Effects of 9/11‐related injury on retirement patterns among World Trade Center Health Registry enrollees. Issue 10 (1st September 2021) - Seil, Kacie; Yu, Shengchao; Brackbill, Robert; Alper, Howard; Maqsood, Junaid
Abstract: Background: Many survivors of the 9/11/2001 terrorist attacks in New York City sustained injuries. The aim of this study was to understand how 9/11‐related injuries affected retirement patterns of World Trade Center Health Registry enrollees. Methods: The study included enrollees who participated in the 2017 Health & Quality of Life Survey, focused on 9/11‐related injuries and quality of life, and the 2017–2018 Health & Employment Survey, focused on retirement and employment ( N = 3535). Using Cox proportional hazards and logistic regression modeling, we calculated the risk of retiring at earlier ages and the odds of retirees working again, controlling for relevant covariates. Results: Results showed that 9/11‐related injuries did affect retirement patterns. Injured enrollees were at greater risk of retiring at younger age compared to non‐injured enrollees. Compared to more severely injured retirees, non‐injured and less severely injured retirees were significantly more likely to work again postretirement. Our results suggested that being injured on 9/11 was associated with retirement, meaning that if the injury had not occurred, the individual may have continued working longer. Conclusions: The need to retire earlier than planned could be addressed with employer and societal changes. Employers should consider making accommodations for those impacted by 9/11 a priority, as it is imperative for those who were injured on 9/11 to have the ability to work to support their physical, mental, and financial well‐being.